Evaluation of the Physicochemical Properties of Noodles with Various Processing Methods of Yellowtail Scad (Selaroides leptolepis cuvier): Evaluasi Sifat Fisikokimia Mi Dengan Berbagai Metode Pengolahan Pada Ikan Selar Kuning (Selaroides leptolepis cuvier) - Jenri Parlinggoman Hutasoit; Kharismayati (Department of Food Science and Biotechnology, Faculty of Agroindustrial and Biosystem Technology, Universitas Brawijaya, 2026)
Noodles are a popular food product typically made from carbohydrates and plant-based proteins. Still, they can also be modified with animal protein. This study aimed to determine the effects of different processing methods for yellowstripe scad on the nutritional value and physical properties of the resulting noodles. Five processing methods were tested: steaming, baking, boiling, frying, and control. The parameters tested included moisture content, fat, protein, carbohydrates, energy, expansion volume, water absorption, and weight loss of the noodles. The results showed that the steaming method retained the highest levels of nutrients (protein 17.88%, carbohydrates 63.23%, energy 414.80 kcal), although it had the lowest expansion volume and water absorption. Frying increased the expansion volume and water absorption but decreased the protein, carbohydrate, ash, and energy content. High-temperature processing influenced the physicochemical changes in theresulting noodles. Abstrak Mi merupakan produk pangan populer yang biasanya terbuat dari karbohidrat dan protein nabati, namun dapat dimodifikasi dengan protein hewani. Penelitian ini bertujuan untuk mengetahui pengaruh metode pengolahan daging ikan selar kuning terhadap nilai nutrisi dan sifat fisik mi. Lima metode pengolahan diuji: pengukusan, pengovenan, perebusan, penggorengan, dan kontrol. Parameter yang diuji mencakup kadar air, lemak, protein, karbohidrat, energi, volume pengembangan, daya serap air, dan susut bobot mi. Hasil menunjukkan bahwa metode pengukusan mempertahankan nutrisi terbaik (protein 17,88%, karbohidrat 63,23%, energi 414,80 kkal), meski memiliki volume pengembangan dan daya serap air terendah. Penggorengan meningkatkan volume pengembangan dan daya serap air, namun menurunkan kandungan protein, karbohidrat, abu, dan energi.Pengolahan dengan suhu tinggi berpengaruh pada perubahan fisiko-kimia mi yang dihasilkan.